Effective Removal of Microplastics Using a Process of Ozonation Followed by Flocculation with Aluminum Sulfate and Polyacrylamide - Jie Wang; Meiyi Hu; Ziyi Zhang; Shaoping Tong (Separations, 2025)
The widespread use of plastics in our daily life has caused many health problems. Conventional water treatment processes have low efficiency in the removal of microplastics from water. In this work, we investigated the efficiency of ozonation pretreatment followed by flocculation to remove microplastics from water. After the ozonation pretreatment, it was found that microplastic removal could be significantly enhanced by flocculation from 40% to 91%. The characterization results show that the ozonation-pretreated microplastics had rougher surfaces and larger amounts of surface hydroxyl groups and carbonyls, which might be responsible for their increased removal. However, there was still a small amount of microplastics that had not been removed. They floated on the surface of the solution and could not be effectively oxidized by ozone, thus not changing their surface properties. This further confirms the importance of hydroxyl groups.